ANALISIS NILAI-NILAI MODERASI BERAGAMA DALAM KEGIATAN EKSTRAKURIKULER - Anggi Putri Utami; Syarnubi Syarnubi; Mardeli Mardeli; Nyayu Soraya; Irja Putra Pratama; Alimron Alimron; Padli Padli (PAI RAFAH, 2023)
This research discusses the Analysis of Religious Moderation Values in Extracurricular Activities at Nurul Amal Junior High School Palembang. The purpose of this study was to determine the values of religious moderation in extracurricular activities at Nurul Amal Junior High School Palembang and to find out the supporting and inhibiting factors of religious moderation values in extracurricular activities at Nurul Amal Junior High School Palembang. The type of research used by researchers is qualitative research. Data collection methods by means of observation, interviews and documentation. The type of observation carried out is participant observation and the type of interview used is in-depth interview. The data analysis technique is to use data reduction and data presentation and conclusions. The results of this study indicate that the values of religious moderation contained in extracurricular activities at Nurul Amal Junior High School Palembang are the value of national commitment students are taught to foster love for the country. The value of tolerance is instilled in students, so that students can respect and appreciate each other with the differences that exist, both between people of the same religion and between religious communities. Supporting factors for the values of religious moderation in extracurricular activities are the principal and the teachers who supervise extracurricular activities, who play an active role in supporting the values of religious moderation and adequate infrastructure. Meanwhile, the inhibiting factor is the lack of implementation time and the lack of enthusiasm of some students to participate in Islamic spiritual extracurricular activities.